Study of Photo and Thermoluminescence Properties to Identify Irradiated Dried-Fishery Products. Issue 3 (2nd April 2016) - Kim, Moon-Young; Ahn, Jae-Jun; Akram, Kashif; Kim, Gui-Ran; Jeong, Mi-Seon; Kwak, Ji-Young; Kwon, Joong-Ho
ABSTRACT: Radiation-specific luminescence properties in irradiated dried-fishery products (pollack, little pollack, clams, and shrimp) were investigated at different dose levels (0–10 kGy). Photostimulated luminescence (PSL) analysis of whole samples was effective for dried clams and shrimp, while low PSL sensitivity was observed in dried pollack and little pollack. Thermoluminescence (TL) analysis was conducted after isolation of silicate minerals, in which the two methods of mineral isolation—density separation and acid hydrolysis—were compared. Irradiated samples were easily distinguishable through the strong TL glow curves, with maximum peaks in temperature range of 150–250°C. TL ratios (TL1 /TL2 ) were < 0.1 for nonirradiated samples, while > 0.1 for irradiated. There was a clear effect of applied irradiation dose, with a negligible effect of the method used for mineral separation. The mineral composition showed that feldspar and quartz minerals were mainly responsible for the well-characterized luminescence behavior upon irradiation.